Performance Evaluation of Sort Algorithm - Bhardwaj, Sahil; Malik, Sachin; Munjal, Sahil (IJRDO -Journal of Computer Science Engineering, 2015)
This research paper presents performance evaluation of Sort Algorithms like Insertion, Merge Sort and gives their performance analysis with respect to time complexity. These two algorithms has been an area of focus for a long time but still the question remains the same of “which to use when?” which is the main reason to perform this research. This research provides a detailed study of how all the four algorithms work and then compares them on the basis of various parameters apart from time complexity to reach our conclusion.